The Profile of Autopsy Cases at Rajshahi Medical College - Yesmin, Laila; Uddin, Md Kafil; Islam, Md Rafiqul; Talukdar, Sandwip; Rahman, Md Zubaidur; Debnath, Joya (KYAMC Journal, 2022)
Objective: The objective of the study was to explore the profile of Autopsy cases at Rajshahi Medical College. Materials and Methods: This observational study was carried out at Rajshahi Medical College. From January 2021 to June 2021. A total of 248 autopsy cases were included as a sample size during the study. Results: Most of the autopsy cases were found to be male ( 75% ), More than 40.72% death were due to poisoning, followed by suicidal hanging cases (19.76% ),homicide cases (14.51%), different types of accidental cases( 8.47%). In case of road traffic accidents (RTA) 70% cases were by 2-wheelervehicles followed by 25% were by 4-wheeler vehicles, 3% were by heavy vehicles and 2% were pedestrian cases. Death from suicidal hanging were mostly common in the age group 15-25 years, Homicide in47-67 years, poisoning in 47-67 years, Accidental fall from height in 15-25 years and Natural death in the age group of 67 years and above. Conclusion: This study helps to interpret several sorts of medico-legal situations, by policy makers, health care programmers, judiciary and investigation and then takes appropriate action to minimize mortality. KYAMC Journal. 2022;12(04): 205-207